Development and characterization of graphitic carbon nitride as nonblack filler in natural rubber composites. Issue 42 (14th June 2019) - Bansod, Naresh D.; Roy, Kumarjyoti; Das, Chayan; Vidyasagar, Devthade; Potiyaraj, Pranut
ABSTRACT: A new type of elastomeric composite containing natural rubber (NR) and graphitic carbon nitride (g‐C3 N4 ) has been successfully prepared with the reinforced property. The reinforcing effect of g‐C3 N4 in NR composites was examined by cure, mechanical, morphological, and swelling studies. Besides, epoxidized NR with 50‐mol % epoxy level (ENR‐50) was used as a compatibilizer to enhance the hydrophilic g‐C3 N4 filler capacity for hydrophobic NR composites. At the same filler load level, the mechanical properties of NR/g‐C3 N4 composites, such as tensile strength and tensile modulus, were consistently increased with increased ENR‐50 content. To note, the ENR compatibilized composites have shown better‐reinforced performance, which has been attributed to the hydrogen bonding interactions between the uncondensed amine groups in g‐C3 N4 and the polar groups in ENR. We believe that these newly prepared NR composites based on g‐C3 N4 as nonblack filler and ENR‐50 as compatibilizer can find potential applications in modern day rubber research. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 48136. Abstract :